Azathioprine-induced interstitial nephritis in an anti-neutrophil cytoplasmic antibody (ANCA) myeloperoxidase (MPO) vasculitis patient - Pires da Rosa, Gilberto (2018)
Azathioprine (AZA) is used in a wide array of autoimmune diseases, still corresponding to the mainstay maintenance therapy in anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitides. Although generally well-tolerated, several side effects are recognized. We report the case of a 50-year-old Caucasian man with kidney-limited ANCA myeloperoxidase (MPO) vasculitis who presented with general malaise, fever, worsening renal function, and elevated inflammatory markers 2 weeks after the initiation of therapy with oral AZA. Although a disease relapse was suspected, renal biopsy revealed an eosinophilic infiltrate, suggestive of acute interstitial nephritis. After suspension of AZA, a sustained improvement of renal function and normalization of inflammatory markers was observed. A diagnosis of allergic interstitial nephritis secondary to AZA was established, corresponding to the first biopsy-proven case described in an ANCA MPO vasculitis patient. Although rare, renal toxicity of AZA must be present in the clinician's mind, avoiding the straightforward assumption of disease relapse in the case of worsening renal function.